Association Between White Matter Connectivity and Early Dementia in Patients With Parkinson Disease. (3rd May 2022) - Chung, Seok Jong; Kim, Yae Ji; Jung, Jin Ho; Lee, Hye Sun; Ye, Byoung Seok; Sohn, Young H.; Jeong, Yong; Lee, Phil Hyu
Abstract : Background and Objectives: Several clinical and neuroimaging biomarkers have been proposed to identify individuals with Parkinson disease (PD) who are at risk for ongoing cognitive decline. This study aimed to explore whether white matter (WM) connectivity disruption is associated with dementia conversion in patients with newly diagnosed PD with mild cognitive impairment (PD-MCI). Methods: Seventy-five patients with drug-naive PD-MCI who underwent serial cognitive assessments during the follow-up period (>5 years) were enrolled for the neuroimaging analyses. The patients were classified into either the PD with dementia (PDD) high-risk group (PDD-H, n = 38) or low-risk group (PDD-L, n = 37), depending on whether they converted to dementia within 5 years of PD diagnosis. We conducted degree-based statistic analyses based on a graph-theoretical concept to identify the subnetworks whose WM connectivity was disrupted in the PDD-H group compared with the PDD-L group. Results: The PDD-H group showed poorer cognitive performance on frontal/executive, visual memory/visuospatial, and attention/working memory/language function than the PDD-L group at baseline assessment. The PDD-H group exhibited more severely disrupted WM connectivity in both frontal and posterior cortical regions with 8 hub nodes in the degree-based statistic analysis. The strength of structural connectivity within the identified subnetworks was correlated with the composite scores of frontal/executive function domain (γ = 0.393) and the risk score of PDD conversion within 5 years (γ = −0.480). Discussion: This study demonstrated that disrupted WM connectivity in frontal and posterior cortical regions, which correlated with frontal/executive dysfunction, is associated with early dementia conversion in PD-MCI. Classification of Evidence: This study provides Class II evidence that disrupted WM connectivity in frontal and posterior cortical regions is associated with early dementia conversion in PD-MCI.